(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
R & D in a country is essential for self-reliance in many fields and defence sector is a major participant in it. India is highly dependent on foreign countries for its defence weapon system needs and is a major importer of arms. The paper discusses in detail the R&D environment in India compared to global trends and what needs to be done to improve the situation so that the country becomes self-reliant to a large degree on its weapon needs.